STUDY OF THE ECONOMIC CONTENT OF INCOME FOR THE PURPOSES OF ACCOUNTING AND MANAGEMENT IN AN INDUSTRIAL ENTERPRISE - BONDARENKO, Natalya; HAVRYLENKO, Olha (Herald of Khmelnytskyi National University. Economic sciences, 2023)
The effectiveness of management decisions largely depends on timely receipt of information about economic operations. The main source of such information is accounting. A properly organized income accounting system has a significant impact on the strategic success of business entities, since the formation of the financial result of the enterprise and its further functioning in the long term depends on it. The purpose of the article is to study the essence of the accounting and economic category "income" and determine the place of income in the accounting and management system at an industrial enterprise. The article highlights the views of scientists regarding the economic meaning of the concept of "income". An analysis of the definition of "income" in regulatory, accounting and economic sources was carried out, on the basis of which it was established that the accounting approach to the essence of income is based on the term "economic benefit". Highlighting a unified approach to the essence of income allows you to emphasize the importance of this category for accounting and forming reporting indicators. The results of the conducted research showed that the lion's share of income falls on income from operational activities, thereby emphasizing their importance in industrial enterprises. For effective management of operating income, it is important to have a high-quality classification of them. A meaningful classification of operating income plays a leading role in the accounting and management system at an industrial enterprise. The classification system should be flexible and quickly adapt to the needs of information users in order to make effective management decisions. However, industrial enterprises have significant features of their activities, therefore, when classifying income, the specifics of various branches of the industrial sector must be taken into account.
Keywords: income; profit; revenue; accounting; management